1977
DOI: 10.1103/physrevb.15.3565
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orientation diagram of the pseudobinaryTb1xDyxFe

Abstract: Comments and AddendaThe section Comments and Addenda is for short communications which are not appropriate for regular articles. It includes only the following types of communications: (I) Comments on papers previousLy published in The Physical Review or Physical Review Letters.(2) Addenda to papers previously published in The Physical Review or Physical Review Letters, in which the additional information abstract for information-retrieval purposes. Accepted manuscripts folio~the same publication schedule as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0
2

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 6 publications
3
14
0
2
Order By: Relevance
“…Our measurements are summarized in the phase diagram of Fig. 1 and compared with previous measurements [11,12] plus the results of single ion crystal field theory. We find that the MPB region, across which phases coexist, widens with increasing temperature.…”
mentioning
confidence: 86%
“…Our measurements are summarized in the phase diagram of Fig. 1 and compared with previous measurements [11,12] plus the results of single ion crystal field theory. We find that the MPB region, across which phases coexist, widens with increasing temperature.…”
mentioning
confidence: 86%
“…Similar to ferroelectric MPBs, the already reported Tb 1Àx Dy x Co 2 6 and Tb 1Àx Dy x Fe 2 7 systems also show the flattened free energy landscape, which results in the coexistence of two low-symmetry phases and the significantly enhanced fieldinduced strain at MPB. Consequently, this offers a magnetostructural origin for the well-known Terfenol-D giant magnetostrictive materials (GMMs) with compositions near MPB (typically, Tb 0.3 Dy 0.7 Fe 2 ) , [9][10][11][12] which can generate high magnetostriction at low switching fields. MPB in Tb 1Àx Dy x Fe 2 was previously known as a "spin-orientation transition" that has been explained by single-ion theory, 10 but how maximum magnetostriction appears is unclear.…”
mentioning
confidence: 99%
“…Previously, it has been long believed that this alloy keeps C15 MgCu 2 -type cubic Laves phase structure across each transition, which is known as the Curie transition and spin reorientation transition (SRT), respectively. 10 Recent precise electrical and thermal measurements have demonstrated that the Curie transition has first-order features, i.e., small thermal hysteresis and latent heat. 24 The structure for Tb 0.3 Dy 0.7 Fe 2 below Curie temperature T C is thus having lower crystal symmetry.…”
mentioning
confidence: 99%
“…Редкоземельные фазы Лавеса RT 2 (R -редкоземельный элемент; T -3d-переходный металл) уже более полувека вызывают большой интерес специалистов в области как физики конденсированных сред, так и функциональных материалов, благодаря разнообразию наблюдаемых в них физических явлений, таких как гигантская магнитострикция, магнитокалорический и магнитоэлектрический эффекты [1][2][3][4][5][6][7][8][9][10]. Наиболее известной является система TbFe 2 −DyFe 2 , в которой при определенных условиях состава и температуры можно достичь компенсации магнитокристаллической анизотропии (МКА) и получить состав с гигантскими значениями магнитострикции (λs ∼ 2000 ppm) в слабых магнитных полях в широкой области температур.…”
Section: Introductionunclassified
“…Наиболее известной является система TbFe 2 −DyFe 2 , в которой при определенных условиях состава и температуры можно достичь компенсации магнитокристаллической анизотропии (МКА) и получить состав с гигантскими значениями магнитострикции (λs ∼ 2000 ppm) в слабых магнитных полях в широкой области температур. В области комнатной температуры таким составом является Tb 0.3 Dy 0.7 Fe 2 , известный как Терфенол-D [2,6]. Данный материал широко используется в высокочувствительных датчиках, источниках ультразвука и других механизмах [11][12][13].…”
Section: Introductionunclassified